Optical Multiplexing Anti-Counterfeiting Film Based on Self-Assembled and Holography Lithographic Photonic Architectures - Xiaowan Xu; Yanjun Liu; Dan Luo (IEEE Photonics Journal, 2022)
Multiplexing anti-counterfeiting technologies based on micro/nano structural colors of photonic crystals have been proposed for information security because of unduplicability and diversity. However, most of current fabrication methods for micro/nano structural color such as electronic beam etching and ordered nanoparticles are accompanied with expensive and complex fabrication process. Reliable multiplexing anti-counterfeiting technologies with low cost and easy-fabrication process for currency, brands and information security remain a long-time and innovative challenge. Herein, a simple strategy to fabricate optical multiplexing anti-counterfeiting film based on self-assembled three-dimensional photonic crystal BPLC encoded with holography lithographic 1D/2D surface photonic crystal has been proposed. The proposed bilayer structure can exhibit multi-images with different angles in 3D space, leading to multiple encryptions with information protection or access permission. Quick response (QR) code with cryptographic functionality through our proposed multiplexing anti-counterfeiting film based on bilayer structural color is also demonstrated. The proposed strategy for optical multiplexing anti-counterfeiting film is low-cost, easy-fabricated, time saving, stable and flexible, capable for promising perspective in information security level and storage density, and offering potential application in anti-counterfeiting.